The Ribosome Restrains Molten Globule Formation in Stalled Nascent Flavodoxin - Houwman, Joseline A. (J Biol Chem, 2016)
Folding of proteins usually involves intermediates, of which an important type is the molten globule (MG). MGs are ensembles of interconverting conformers that contain (non-)native secondary structure and lack the tightly packed tertiary structure of natively folded globular proteins. Whereas MGs of various purified proteins have been probed to date, no data are available on their presence and/or effect during protein synthesis. To study whether MGs arise during translation, we use ribosome-nascent chain (RNC) complexes of the electron transfer protein flavodoxin. Full-length isolated flavodoxin, which contains a non-covalently bound flavin mononucleotide (FMN) as cofactor, acquires its native α/β parallel topology via a folding mechanism that contains an off-pathway intermediate with molten globular characteristics. Extensive population of this MG state occurs at physiological ionic strength for apoflavodoxin variant F44Y, in which a phenylalanine at position 44 is changed to a tyrosine. Here, we show for the first time that ascertaining the binding rate of FMN as a function of ionic strength can be used as a tool to determine the presence of the off-pathway MG on the ribosome. Application of this methodology to F44Y apoflavodoxin RNCs shows that at physiological ionic strength the ribosome influences formation of the off-pathway MG and forces the nascent chain toward the native state.